Interictal Hyperperfusion in the Higher Visual Cortex in Patients With Episodic Migraine. Issue 10 (4th November 2019) - Michels, Lars; Villanueva, Jeanette; O'Gorman, Ruth; Muthuraman, Muthuraman; Koirala, Nabin; Büchler, Roman; Gantenbein, Andreas R.; Sandor, Peter S.; Luechinger, Roger; Kollias, Spyros; Riederer, Franz
Abstract : Background: Migraine pathophysiology is complex and probably involves cortical and subcortical alterations. Structural and functional brain imaging studies indicate alterations in the higher order visual cortex in patients with migraine. Arterial spin labeling magnetic resonance imaging (ASL‐MRI) is a non‐invasive imaging method for assessing changes in cerebral blood flow (CBF) in vivo . Objective: To examine if interictal CBF differs between patients with episodic migraine (EM) with or without aura and healthy controls (HC). Methods: We assessed interictal CBF using 2D pseudo‐continuous ASL‐MRI on a 3 Tesla Philips scanner (University Hospital Zurich, Switzerland) in EM (N = 17, mean age 32.7 ± 9.9, 13 females) and HC (N = 19, mean age 31.0 ± 9.3, 11 females). Results: Compared to HC, EM showed exclusively hyperperfusion in the right MT+ and Cohen's d effect size was 0.99 (HC mean CBF ± SD: 33.1 ± 5.9 mL/100 g/minutes; EM mean CBF: 40.9 ± 9.4 mL/100 g/minutes). EM with aura (N = 13, MwA) revealed hyperperfusion compared to HC in the right MT+ and superior temporal gyrus. For MT, Cohen's d effect size was 1.34 (HC mean CBF ± SD: 33.1 ± 5.9 mL/100 g/minutes; MwA mean CBF: 43.3 ± 8.6 mL/100 g/minutes). For the superior temporal gyrus, Cohen's d effect size was 1.28 (HC mean CBF ± SD: 40.1 ± 4.9 mL/100 g/minutes; MwA mean CBF: 47.4 ± 6.4 mL/100 g/minutes). In EM, anxiety was positively associated with CBF in the parietal operculum and angular gyrus. Conclusions: Our results suggest that extrastriate brain regions probably involved in cortical spreading depression are associated with CBF changes in the interictal state. We conclude that ASL‐MRI is a sensitive method to identify local neuro‐functional abnormalities in CBF in patients with EM in the interictal state.